2018
DOI: 10.1262/jrd.2017-160
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-related consequences of heat stress exposure during bovine oocyte maturation persist in early embryo development

Abstract: Hyperthermia during estrus has direct consequences on the maturing oocyte that carries over to the resultant embryo to compromise its ability to continue in development. Because early embryonic development is reliant upon maternal transcripts and other ooplasmic components, we examined impact of heat stress on bovine oocyte transcripts using microarray. Oocytes were matured at 38.5ºC for 24 h or 41.0ºC for the first 12 h of in vitro maturation; 38.5ºC thereafter. Transcriptome profile was performed on total (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 61 publications
0
31
2
Order By: Relevance
“…In bovine oocytes, exposing oocytes to high temperature (41°C) during the first 6 hr of IVM increased mitochondrial ROS levels, whereas cytoplasmic ROS levels decreased compared with controls (Payton et al, ). After 12 hr of high thermal exposure, oocyte developmental competence is compromised and apoptosis increases within the inner cell mass (ICM) cells of the blastocysts obtained from HS oocytes (Ascari et al, ).…”
Section: The Female Reproductive Tractmentioning
confidence: 99%
“…In bovine oocytes, exposing oocytes to high temperature (41°C) during the first 6 hr of IVM increased mitochondrial ROS levels, whereas cytoplasmic ROS levels decreased compared with controls (Payton et al, ). After 12 hr of high thermal exposure, oocyte developmental competence is compromised and apoptosis increases within the inner cell mass (ICM) cells of the blastocysts obtained from HS oocytes (Ascari et al, ).…”
Section: The Female Reproductive Tractmentioning
confidence: 99%
“…Rearrangement of the mitochondria during maturation is associated with increased mitochondrial polarity and activity, and these have been found to be altered by seasonal thermal stress and associated with reduced embryonic development (Gendelman & Roth, ). Recently, Payton et al () reported that exposing bovine oocytes to heat shock (41°C) during in vitro maturation impairs mitochondrial reactive oxygen species, glutathione and ATP contents in the oocyte. Interestingly, the oocyte ATP content increased upon exposure to heat stress (41°C for 24 hr) and persisted in 8‐ to 16‐cell embryos, but not in the blastocyst, suggesting a long‐lasting effect on mitochondrial function through the early cleavage stages of embryonic development.…”
Section: Heat Stressmentioning
confidence: 99%
“…Recent studies have provided new insight into the molecular alterations induced by heat shock, including impairments in both maternal and mitochondrial transcripts (Ferreira et al, ; Gendelman & Roth, , ; Payton et al, , ). These observations could clarify, in part, the mechanism underlying the response of the oocyte to heat stress and the further consequences in the developing embryo.…”
Section: Heat Stressmentioning
confidence: 99%
See 2 more Smart Citations